New species in aquaculture: are the striped venus clam Chamelea gallina (Linnaeus, 1758) and the surf clam Spisula solida (Linnaeus 1758) potential candidates for diversification in shellfish aquaculture?. (1st October 2014) - Joaquim, Sandra; Matias, Domitília; Matias, Ana Margarete; Gonçalves, Rui; Chícharo, Luís; Gaspar, Miguel B
Abstract: The surf Spisula solida and the striped venus Chamelea gallina clams support important fisheries in Europe. These fisheries have been affected by inter‐annual fluctuations in stock abundance and recruitment failures. Aquaculture could contribute to address these problems through the production of larvae or juveniles for stock‐enhancement programmes. In the present study, the prerequisites to produce these species in hatchery were established. Of the different methods used to obtain gametes (thermal stimulation, scarification and flow through), C. gallina spawned in the flow through only. By its turn, the best method for obtaining gametes for S. solida was stripping. Higher survivals of D‐larvae were found at 15 and 17°C. The greatest larval survival and growth rates were obtained from larvae fed Isochrysis aff. galbana ( T‐iso ). First C. gallina and S. solida pediveliger larvae were found at day 8 and day 26 respectively. The presence of metamorphosed larvae found even in the unfed treatment for C. gallina and for S. solida is an advantage for aquaculture production. After metamorphosis, the S. solida juveniles' survival was quite low, whereas there was no mortality for C. gallina juveniles reared without substrate regardless the diet provided. Juveniles fed the binary diet ( Chaetoceros calcitrans ‐ C. cal + T.iso ) and the monodiet T‐iso showed relatively higher growth in shell length and weight than C. cal . The hatchery production of these two species was possible, however the results of this study showed that C. gallina can be more attractive for aquaculture than S. solida .